马来西亚华人玩家的游戏语言选择调查 = An investigation of language preference in Chinese Malaysian gaming community - 赖政墀 Lai, Zheng Ci (Nanyang Technological University, 2020)
马来西亚是个多元语言文化的国家，其中华人占了总人口约2成，基本上都以马来西亚华语为母语，并且能够看懂和使用简体中文和繁体中文。作为汉语的地区变体之一，马来西亚华语在语音、语法、词汇上都与其他的地区变体不尽相同。 游戏在中文本地化的过程中，简体中文和繁体中文的译文目标玩家群基本上分别是中国大陆和港澳台地区的玩家。对于马来西亚华人玩家而言，无论选择哪一个语言都无法得到完善的游玩体验。 本文将以《星露谷物语》的简体中文版和巴哈姆特论坛上网友自发自制的繁体中文版模组进行比较，借由调查问卷的方式，讨论现有的简体中文版游戏对马来西亚华人玩家的适用性。同时，也借助两个版本的译文，讨论马来西亚华人玩家对游戏翻译质量的要求。 最后，我们分析玩家们的意见，进一步讨论在未来推出马来西亚华语版游戏的可能性。 Malaysia is a multilingual and multicultural country, with the Chinese making up about 20% of the total population. Most of them are native speaker of Malaysian Chinese, and able to understand and use both Simplified Chinese and Traditional Chinese. As one of the regional varieties of Chinese, Malaysian Chinese is different from other regional varieties in terms of pronunciation, grammar as well as vocabulary. During the process of game localization for Chinese, the target players of the Simplified Chinese version are basically players from Mainland China while the Traditional Chinese version target players from Hong Kong, Macau or Taiwan. For Chinese Malaysian gamer, they can never have a complete gaming experience regardless of their choices of language. In order to understand the applicability of the existing Simplified Chinese version of a game to Chinese Malaysian players, a survey was conducted to Chinese Malaysian gamers so as to discover their preference between the Simplified Chinese version of Stardew Valley and the Tradition Chinese version modules which was made by users from forum.gamer.com.tw. The player’s demands for quality of translation were also discussed. Finally, opinions of the players were analysed to further explore the potentiality of launching Malaysian Chinese as a gaming language in the future.